MuRF1 deficiency prevents age‐related fat weight gain, possibly through accumulation of PDK4 in skeletal muscle mitochondria in older mice. Issue 5 (9th July 2021) - Sugiura, Kosuke; Hirasaka, Katsuya; Maeda, Tasuku; Uchida, Takayuki; Kishimoto, Koji; Oarada, Motoko; Labeit, Siegfried; Ulla, Anayt; Sakakibara, Iori; Nakao, Reiko; Sairyo, Koichi; Nikawa, Takeshi
Abstract: Recent studies show that muscle mass and metabolic function are interlinked. Muscle RING finger 1 (MuRF1) is a critical muscle‐specific ubiquitin ligase associated with muscle atrophy. Yet, the molecular target of MuRF1 in atrophy and aging remains unclear. We examined the role of MuRF1 in aging, using MuRF1‐deficient (MuRF1 –/– ) mice in vivo, and MuRF1‐overexpressing cell in vitro. MuRF1 deficiency partially prevents age‐induced skeletal muscle loss in mice. Interestingly, body weight and fat mass of more than 7‐month‐old MuRF1 –/– mice were lower than in MuRF1 +/+ mice. Serum and muscle metabolic parameters and results of indirect calorimetry suggest significantly higher energy expenditure and enhanced lipid metabolism in 3‐month‐old MuRF1 –/– mice than in MuRF1 +/+ mice, resulting in suppressed adipose tissue gain during aging. Pyruvate dehydrogenase kinase 4 (PDK4) is crucial for a switch from glucose to lipid metabolism, and the interaction between MuRF1 and PDK4 was examined. PDK4 protein levels were elevated in mitochondria from the skeletal muscle in MuRF1 –/– mice. In vitro, MuRF1 interacted with PDK4 but did not induce degradation through ubiquitination. Instead, SUMO posttranscriptional modification (SUMOylation) of PDK4 was detected in MuRF1‐overexpressing cells, in contrast to cells without the RING domain of MuRF1. MuRF1 deficiency enhances lipid metabolism possibly by upregulating PDK4 localization into mitochondrial through prevention of SUMOylation. Inhibition of MuRF1‐mediated PDK4 SUMOylation is a potential therapeutic target for age‐related dysfunction of lipid metabolism and muscle atrophy. Abstract :